2020
DOI: 10.1002/adfm.202005066
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Cubic Boron Nitride: A Noncytotoxic Ultrahard Material

Abstract: Cubic boron nitride (c‐BN) has an ultrahardness and a large bandgap energy like diamond. In the last 30 years, most of the attention has been directed towards the mechanical and electronic applications of c‐BN, while its biological potential has been overlooked. The authors report in vitro biocompatibility of high‐quality c‐BN films prepared by plasma‐enhanced chemical vapor deposition using the chemistry of fluorine. c‐BN films become superhydrophilic when chemical‐treated in hydrogen and nitrogen plasmas wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The measured contact angles of polar deionized water and apolar 1-bromonaphthalene were used to calculate the polar (γ p ) and dispersive (γ d ) components of the apparent surface free energy of CNWs by the Owens and Wendt method . The sum of γ p = 2.6 mJ m –2 and γ d =18.8 mJ m –2 typical of ethanol was actually much lower than γ p ≈ 0 mJ m –2 and γ d 44 mJ m –2 (above the measurable limit) calculated for CNWs . Since diamond nanoparticles can adsorb onto the contact area of dispersion media only, higher wettability enables adsorption of particles more evenly on CNWs with less aggregation/coalescence.…”
Section: Resultsmentioning
confidence: 98%
“…The measured contact angles of polar deionized water and apolar 1-bromonaphthalene were used to calculate the polar (γ p ) and dispersive (γ d ) components of the apparent surface free energy of CNWs by the Owens and Wendt method . The sum of γ p = 2.6 mJ m –2 and γ d =18.8 mJ m –2 typical of ethanol was actually much lower than γ p ≈ 0 mJ m –2 and γ d 44 mJ m –2 (above the measurable limit) calculated for CNWs . Since diamond nanoparticles can adsorb onto the contact area of dispersion media only, higher wettability enables adsorption of particles more evenly on CNWs with less aggregation/coalescence.…”
Section: Resultsmentioning
confidence: 98%
“…To get better visualization, high resolution XRD was performed at 2θ of 40–50°. The broad peak at 41–45° was resolved into two peaks which corresponds to w -BN (002) and c -BN (111) [ 15 , 42 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another interesting property of c -BN is its transparency to a broad range of electromagnetic radiation from the ultraviolet to the infrared [ 14 ]. The above-mentioned outstanding properties of c -BN and w -BN make it a very promising candidate for hard coatings in grinding and cutting tools, electronic and optoelectronic device applications such as deep-ultraviolet detectors, light-emitting diodes, high-power/high-speed transistors for operation at high temperatures in harsh environments, and UV–Vis–IR transparent optical devices such as lenses and windows [ 3 , 14 , 15 , 16 ]. It has recently been reported that c -BN can be biocompatible and non-cytotoxic, and can be used as a novel scaffold for biomedical applications [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To solve the conflict between early osseointegration and long-term fixation of the soluble ceramics coated implants to bone, persistent efforts to seek alternative strategies instead of dissolution-derived activation are currently carrying out. Especially, boron nitride [ 16 ] as well as nanostructured titania [ 17 ] and hydrogen titanates [ 18 ], all being insoluble, have been recently developed to act respectively as hydrophilic activation and topographic activation of metal implants, drawing a paradigm for activation without dissolution of coatings.…”
Section: Introductionmentioning
confidence: 99%